2015
DOI: 10.1016/j.ydbio.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Xenopus laevis spinal cord requires Sox2/3 expressing cells

Abstract: Spinal cord regeneration is very inefficient in humans, causing paraplegia and quadriplegia. Studying model organisms that can regenerate the spinal cord in response to injury could be useful for understanding the cellular and molecular mechanisms that explain why this process fails in humans. Here, we use Xenopus laevis as a model organism to study spinal cord repair. Histological and functional analyses showed that larvae at pre-metamorphic stages restore anatomical continuity of the spinal cord and recover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
98
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(115 citation statements)
references
References 87 publications
13
98
0
Order By: Relevance
“…Interestingly, in a study of the effect of thyroid hormone T3 on cell proliferation, it was observed that the number of proliferating cells during premetamorphosis and early prometamorphosis was similar in different brain regions (stages 52–55), with an increase in the number of proliferative cells later in development (Denver et al, 2009). In addition, it was also described that at stages 50–54 the Xenopus larvae show a strong regenerative capacity, which is no longer present later, probably related to the number of dividing precursor cells (Muñoz et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in a study of the effect of thyroid hormone T3 on cell proliferation, it was observed that the number of proliferating cells during premetamorphosis and early prometamorphosis was similar in different brain regions (stages 52–55), with an increase in the number of proliferative cells later in development (Denver et al, 2009). In addition, it was also described that at stages 50–54 the Xenopus larvae show a strong regenerative capacity, which is no longer present later, probably related to the number of dividing precursor cells (Muñoz et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Two types of approaches were used: (1) for neural birth dating BrdU (Sigma B5002) was administered to stages 28, 31 and 37/38 (embryonic stages before the pallial telencephalic evagination; see Table 1 ) by immersion for 30 min at room temperature in 20 mM BrdU in 0,1X Marc’s Modified Ringers (MMR: 1 M NaCl; 20 mM KCl; 10 mM MgCl2;20 mM CaCl2; 50 mM HEPES, pH 7.5), following the protocol previously described Quick and Serrano (2007), Denver et al (2009), and Muñoz et al (2015). The embryos then developed until stage 40 or stage 46, in which the pallial evagination is in process or already completed, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the pituitary is found in a pocket in the ventromedial region of the brain and is not readily separated by accident from the rest of the brain in this procedure. The spinal cord can also be harvested (Muñoz et al 2015).…”
Section: Brain (Fig 1b)mentioning
confidence: 99%
“…Among aquatic vertebrate model animals, Xenopus excels by having comparable organ development and morphology to mammalian systems, but with the added benefit of being able to regenerate adult tissues, such as optic nerve, lens, spinal cord and limb tissue (Blitz et al, 2006; Muñoz et al, 2015; Slack et al, 2008). Xenopus animals and oocytes are used extensively to understand normal organ function and disease in humans (Labonne and Zorn, 2015), including cardiac congenital heart disorders and heterotaxy (Boskovski et al, 2013; Duncan and Khokha, 2016; Fakhro et al, 2011; Kaltenbrun et al, 2011; Langdon et al, 2012; 2007), gastrointestinal and pancreatic diseases (Kofent and Spagnoli, 2016; Pearl et al, 2009; 2011; Salanga and Horb, 2015; Womble et al, 2016), endocrine functions and disorders (Buchholz, 2015), kidney disease (Lienkamp, 2016), lung development (Rankin et al, 2011; 2015; Wallmeier et al, 2014), cancer (Chernet and Levin, 2013; Cross and Powers, 2009; Hardwick and Philpott, 2015; Haynes-Gilmore et al, 2014; Van Nieuwenhuysen et al, 2015; Wylie et al, 2015), ciliopathies (Kim et al, 2010; Klos Dehring et al, 2013; Ma et al, 2014), orofacial defects (Dickinson, 2016), and neurodevelopmental disorders (Erdogan et al, 2016; Pratt and Khakhalin, 2013).…”
Section: Introductionmentioning
confidence: 99%